Development of a Novel De-NOx Technology for the Aftertreatment of Ship Exhaust Gases - Savva, Petros G.; Fessas, Yiannis; Efstathiou, Angelos M.; Costa, Costas (My University, 2023)
The shipping industry is the most fuel-efficient means of transporting goods, carrying more than 90% of the global freight task. Ships generally use low quality fuel to reduce costs and, as a result, the sulfur content in the exhaust gas stream is high. Emissions of sulfur oxides (SOx) and nitrogen oxides (NOx) from ships represent about 13% and 12%, respectively, of the global anthropogenic SOx and NOx emissions. In total, 95% of the total maritime NOx emissions are NO (nitric oxide) and 5% are NO2 (nitrogen dioxide). The present work focuses on the development and pilot operation of an advanced novel Selective Catalytic Reduction of NOx with H2 (H2-SCR) technology for the elimination of Nitrogen Oxides (NOx) emitted from ship exhaust gases. For the proper operation of the novel H2-SCR de-NOx unit, two additional conventional technologies were employed for the removal of SO2 and Particulate Matter (PM). In particular, the proposed novel H2-SCR de-NOx technology was combined with a Sea Water Absorption (SWA) unit and an oxidative catalytic system. A pilot unit has been successfully designed, assembled and implemented on a cruise ship for the abovementioned purposes. This effort is considered to be pioneering and is here attempted for the first time worldwide. It was proven, for the first time ever, that the Selective Catalytic Reduction of NOx with the use of H2 as a reducing agent in combination with a suitable catalyst can be considered a suitable NOx-pollution control technology for ships. In particular, it was found that more than 80% of NOx (to N2), 99.8% of SO2 and 72% of PM can be reduced by using the present combined SWA and H2-SCR technologies.
Keywords: depollution; H2-SCR; sea water adsorption; ship emissions